PECULIARITIES OF SUBSTANTIATING THE SELECTION OF PRIORITY RESEARCH DIRECTIONS IN THE FIELD OF CIVIL-MILITARY COOPERATION (Coordinates of Public Administration, 2026)
The article is devoted to the peculiarities of constructing an approach to justifying the choice of a priority direction of research on the mechanism for implementing civil-military cooperation. An analysis of the latest developments has shown that the scientific and applied discourse on this cooperation is currently relevant. Its main principles are determined by the state's sectoral policy: the updated Doctrine of «Civil-Military Cooperation». The mechanism for implementing this cooperation is considered as an open and complex system. Its functioning and development are ensured by an interdisciplinary array of knowledge and practices; the mechanism for implementing this sectoral policy is accompanied by a wide field of research. An empirical typology of research on the mechanism for implementing civil-military cooperation has been constructed. Its typical directions concern: organizational, legal and informational foundations of cooperation; its theory, practice, methodology and history; mechanisms for its implementation, in particular regarding the digitalization of processes, information communications and training of military personnel. Digitalization is considered as a way to strengthen technological advantage on the way to achieving victory over the enemy. Modern directions of digitization research are defined in terms of: situation monitoring, situational awareness, analytical data processing; use of artificial intelligence to analyze the state of the civilian environment, forecasting the development of events in it, professional education and training of military personnel. For a well-founded choice of the priority direction of research, the following were used: the recognized method of hierarchy analysis as a method of expert decision-making; a pragmatic approach to the formulation of the main and five key criteria. Hierarchy analytics is considered and characterized using the example of three alternatives. It is proposed: to improve the considered approach, taking into account its digitalization and the limitations of the hierarchy analysis method; to develop a methodology for verifying the results obtained. They should be used to build a Strategy for implementing the priority direction of research, using SWOT and TWOS analysis methods.